1994
DOI: 10.1259/0007-1285-67-801-848
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of bone ages when performed by radiology registrars: an audit of Tanner and Whitehouse II versus Greulich and Pyle methods

Abstract: This audit analysed the Tanner and Whitehouse II twenty bone (TW2) method of bone age assessment which was used in our department, and compared it with the Greulich and Pyle (GP) method. 50 previous bone ages were independently re-calculated by each of three registrars using both techniques, with the time taken to perform each assessment being recorded. For each method the interobserver variation was analysed in terms of the spread of results. The intraobserver variation in TW2 was determined by comparing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
82
0
5

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(96 citation statements)
references
References 6 publications
6
82
0
5
Order By: Relevance
“…Lastly, bone determinations in this study were analyzed by two senior pediatric radiologists to minimize to some extent the subjectivity and intraobserver variability. The strong concordance in readings is a reflection of proficiency and confirms previous studies indicating that bone age estimations improve with clinical experience (17)(18)(19)(20).…”
Section: Discussionsupporting
confidence: 86%
“…Lastly, bone determinations in this study were analyzed by two senior pediatric radiologists to minimize to some extent the subjectivity and intraobserver variability. The strong concordance in readings is a reflection of proficiency and confirms previous studies indicating that bone age estimations improve with clinical experience (17)(18)(19)(20).…”
Section: Discussionsupporting
confidence: 86%
“…In most cases, the radiologists and pediatricians use the GP atlas, whereas some pediatric endocrinologists use the more finely scaled TW method [7]. Several studies have been published on the intra- and interobserver variance of BA [8,9,10,11]. King et al [8] provide an overview of many of these studies but it is difficult to draw any conclusions from their table because of conflicting results due to differing study designs, differing experience of the raters and differing measures of the interrater variability.…”
Section: Technical and Methodological Considerationsmentioning
confidence: 99%
“…Several studies have been published on the intra- and interobserver variance of BA [8,9,10,11]. King et al [8] provide an overview of many of these studies but it is difficult to draw any conclusions from their table because of conflicting results due to differing study designs, differing experience of the raters and differing measures of the interrater variability. A recent study found a standard error of 0.55 years among the readings of a group of 5 pediatric endocrinologists and a standard error of 0.61 years among 7 radiologists.…”
Section: Technical and Methodological Considerationsmentioning
confidence: 99%
“…In a study conducted by King et al, 50 bone age assessments were performed by 3 evaluators using both the GP and TW2 techniques [7]. In the study, the error margin was determined as 0.74 years for TW2, and as 0.96 years for GP.…”
Section: B Tanner-whitehouse Methodsmentioning
confidence: 99%
“…On the other hand, the GP method is far easier to implement due to its approach based mainly on comparisons of general appearance, which the human visual system is capable of performing quite rapidly. However, it is possible to state that the accuracy rate of this method rests more on the experience of the radiologist.In a study conducted by King et al, 50 bone age assessments were performed by 3 evaluators using both the GP and TW2 techniques [7]. In the study, the error margin was determined as 0.74 years for TW2, and as 0.96 years for GP.…”
mentioning
confidence: 99%